'Candidatus Rickettsia mendelii', a novel basal group rickettsia detected in Ixodes ricinus ticks in the Czech Republic - Hajduskova, Eva; Literak, Ivan; Papousek, Ivo; Costa, Francisco B; Novakova, Marketa; Labruna, Marcelo B; Zdrazilova-Dubska, Lenka (Ticks and tick-borne diseases, 2016)
A novel rickettsial sequence in the citrate synthase gltA gene indicating a novel Rickettsia species has been detected in 7 out of 4524 Ixodes ricinus ticks examined within several surveys performed in the Czech Republic from 2005 to 2009. This new Candidatus Rickettsia sp. sequence has been found in 2 nymphs feeding on wild birds (Luscinia megarhynchos and Erithacus rubecula), in a male tick from vegetation, and 4 ticks feeding on a dog (3 males, 1 female tick). Portions of the ompA, ompB, sca4, and htrA genes were not amplifiable in these samples. A maximum likelihood tree of rickettsiae based on comparisons of partial amino acid sequences of citrate synthase and nucleotide sequences of 16S rDNA genes and phylogenetic analysis revealed a basal position of the novel species in the proximity of R. bellii and R. canadensis. The novel species has been named 'Candidatus Rickettsia mendelii' after the founder of genetics, Gregor Mendel.
Keywords: Ixodes ricinus; Rickettsia Infections; Ticks; RNA, Ribosomal, 16S; nymfa; rickettsiové infekce; psi; Ixodes; Česká republika; Dogs; Tick Infestations; mužské pohlaví; Birds; Candidatus Rickettsia mendelii; Czech Republic; infestace klíšťaty; Bacterial Proteins; Rickettsiae; Citrate (si)-Synthase; Rickettsia; ženské pohlaví; RNA ribozomální 16S; zvířata; Humans; Nymph; epidemiologické monitorování; fylogeneze; Basal group rickettsiae; citrátsynthasa; nemoci přenášené klíšťaty; klíště; Tick-Borne Diseases; ptáci; Epidemiological Monitoring; Female; bakteriální proteiny; Phylogeny; lidé; Male; Animals